RANKL expressions in preservation of surgical tooh extraction treated with Moringa (Moringa oleifera) leaf extract and demineralized freeze-dried bovine bone xenograft - S. Soekobagiono; Adrian Alfiandy; Agus Dahlan (Dental Journal (Majalah Kedokteran Gigi), 2017)
Background: Preservation of sockets is a procedure aimed to reduce bone resorption after tooth extraction. One of the most commonly used xenograft materials is demineralized freeze-dried bone bovine xenograft (DFDBBX). Meanwhile, one of the key regulations in osteoclast genesis process is RANKL bond. A decrease in the number of RANKL expressions can suppress the osteoclast genesis process so that bone resorption can be prevented. The combination of Moringa leaf extract and DFDBBX, as a result, is expected to decrease the number of RANKL. Purpose: This study aimed to measure RANKL expressions in tooth extraction socket treated with Moringa leaf extract combined with DFDBBX. Methods: Fifty six Cavia cobaya rats were divided into eight groups. The first group was a control group with PEG administration onto their extraction sockets. The second group was a treatment group with DFDBBX administration. The third group was a treatment group with Moringa leaf extract administration. The fourth group was a treatment group induced with a combination of DFDBBX and Moringa leaf extract. Examination then was performed on days 7 and 30. After 7 and 30 days, those Cavia cobaya rats were executed and tested with immunohistochemical techniques. Further research data collected then were tested with one-way ANOVA. Results: There were significant differences between the control group and the groups induced with the combination of Moringa leaf extract and DFDBBX. On days 7 and 30, the groups induced with the combination of Moringa leaf extract and DFDBBX had the lowest number of RANKL expressions. Conclusion: The combination of Moringa leaf extract and DFDBBX can decrease the number of RANKL expressions in Cavia cobaya rats on the day 7 and day 30 after tooth extraction.